2021
DOI: 10.1038/s41598-020-80413-y
|View full text |Cite
|
Sign up to set email alerts
|

Preference, performance, and chemical defense in an endangered butterfly using novel and ancestral host plants

Abstract: Adoption of novel host plants by herbivorous insects can require new adaptations and may entail loss of adaptation to ancestral hosts. We examined relationships between an endangered subspecies of the butterfly Euphydryas editha (Taylor’s checkerspot) and three host plant species. Two of the hosts (Castilleja hispida, Castilleja levisecta) were used ancestrally while the other, Plantago lanceolata, is exotic and was adopted more recently. We measured oviposition preference, neonate preference, larval growth, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…This suggests that non-native nectar is a valued resource and that butterflies may prefer non-native flowers over native flowers in some contexts, though a choice experiment could be used to determine this with greater confidence. Our results are similar to a single-species study that found ovipositing females preferred non-native plants (Euphydryas editha; Haan et al, 2021) but are unlike another single-species study that found that nectar foraging adults preferred native flowers (Plebejus icarioides fenderi; Thomas & Schultz, 2016). This reinforces the notion that studies of multiple species offer insights into general tendencies of the community.…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that non-native nectar is a valued resource and that butterflies may prefer non-native flowers over native flowers in some contexts, though a choice experiment could be used to determine this with greater confidence. Our results are similar to a single-species study that found ovipositing females preferred non-native plants (Euphydryas editha; Haan et al, 2021) but are unlike another single-species study that found that nectar foraging adults preferred native flowers (Plebejus icarioides fenderi; Thomas & Schultz, 2016). This reinforces the notion that studies of multiple species offer insights into general tendencies of the community.…”
Section: Discussionsupporting
confidence: 87%
“…mutation rates for viruses), the phenotypic profile of the pathogen (=capacity space), although changing qualitatively and quantitatively under the selective pressure of the new host resource, putatively retain ancestral variants at low frequency in the new host (Figure 4; Figure S2). This outcome provides theoretical support for the retention of the capacity of fast-evolving pathogens to retro-colonize their previous host species by ecological fitting Haan et al, 2021;Janz & Nylin, 1998). RNA viruses, such as SARS-CoV-2, are well known to evolve rapidly through mutation and hybridization (Holland et al, 1982), and the retention of variants may facilitate retro-colonization of humans from other animal species.…”
Section: Discussionmentioning
confidence: 76%
“…Studies comparing butterfly host plant preferences among host plant species often use plants sampled from a single source population (Wehling & Thomspon 1997 ; Ladner and Altizer 2005 ; Haan et al 2021 ; McCarty and Sotka 2013 ; c.f. Singer et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%